Strategi Pembinaan Santri Non-Mukim di Pesantren Jegongan Manfaat - Khoeriyah, Fathul; Alimi, Moh Yasir (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2026)
Contemporary pesantrens have developed in response to modernity and digitalisation. Santri non-mukim, who attend activities at the Jegongan Manfaat pesantren but do not live there, face challenges such as inconsistent commitment, minimal supervision, and attachment to other areas, such as school, work, and family. This study uses Pierre Bourdieu's practice-based theory of habitus, capital, and field to analyse strategies for nurturing non-resident students at the Jegongan Manfaat pesantren. A qualitative research method involving observation, in-depth interviews, and documentation was employed using a case study approach. The results show three main strategies: community-based mentoring through age-based segmentation to strengthen solidarity; an interpersonal approach involving persuasive discussion and personal guidance; and implementing a contemporary Islamic education curriculum that connects religious studies with modern issues. Repetitive social practices and intense interactions allow religious values to be internalised, forming the habitus of non-resident students. These findings emphasise the role of contemporary pesantrens as effective environments for shaping religious attitudes in the face of modern challenges.